Current Concepts and Diagnosis of IgG4-Related Pancreatitis (Type 1 AIP) - Kawa, Shigeyuki (Seminars in Liver Disease, 2016)
Although now considered to be a member of the systemic entity of immunoglobulin G4- (IgG4-) related disease, IgG4-related pancreatitis is generally referred to as type 1 autoimmune pancreatitis (AIP). Type 1 AIP was established based on a pathological background of lymphoplasmacytic sclerosing pancreatitis, high serum IgG4 concentration, and abundant IgG4-bearing plasma cell infiltration. The characteristic clinical features of type 1 AIP, such as elderly male preponderance, obstructive jaundice, and mass-forming lesions in the pancreas, often mimic those of pancreatic cancer. However, because AIP responds favorably to corticosteroid treatment, careful differentiation from pancreatic cancer is required. An AIP diagnosis is currently based on the 2011 International Consensus Diagnostic Criteria for AIP, which are based on high sensitivity, selectivity, and accuracy. Over the long term, AIP can progress to a chronic condition, with pancreatic stone formation and atrophy resembling that of chronic pancreatitis. Although AIP has been linked to the complication of malignancies, it remains controversial whether an association exists between the disease and tumor formation.
Keywords: autoimmune pancreatitis; immunoglobulin G4-related disease; immunoglobulin G4; immunoglobulin G4-related pancreatitis